Association between social capital and HIV treatment outcomes in South Africa - Mukoswa, Grace Musanse (My University, 2016)
Introduction Social capital is seen as “the features of social organization that include civic participation, norms of reciprocity, and trust in others that facilitate cooperation for mutual benefit”. There has been a growing interest in social capital and HIV treatment outcomes. However, the impact of social capital on HIV treatment outcomes remains relatively undefined. The aim of this study was to establish whether social capital is associated with HIV treatment outcomes, particularly ART adherence and virological failure, in HIV patients on ART in South Africa. Materials and Methods This was a cross-sectional analysis of secondary data from a cohort study that investigated how patient outcomes were linked to clinical characteristics. The cohort study was conducted at private and non-governmental (NGO) clinics that were supported by the Aurum Institute for antiretroviral therapy implementation. Participants (n=943) identified by clinic staff as being suitable for inclusion in the study (n=943) were interviewed as they exited from their clinic visit, after giving written informed consent. Questions regarding HIV adherence and perceptions around HIV and health were important determinants of adherence in this population. Participant information was linked with the database. Data analyses included descriptive statistic and logistic regression. Stata computer software version 12 was used for the analysis. Results Being employed and increasing age were found to be associated with social capital (p=0.01 and p=0.07, respectively). The association between social capital and visit non-adherence was not statistically significant. Social capital was, however, significantly associated with unsuppressed viral load at 12 months (OR=0.47; 95% CI=0.25-0.88) and with treatment failure at 12 months (OR=0.59; 95% CI=0.37-0.97) in the univariable analysis. After controlling for age, marital status, education and occupation, higher social capital was still significantly associated with a lower risk of unsuppressed viral load at 12 months (OR=0.48; 95% CI=0.24-0.96) and lower risk of treatment failure at 12 months (OR=0.52; 95% CI=0.32-0.88). Conclusion and Recommendations This study is the first to investigate the association between social capital and HIV treatment outcomes. We found that patients in the study who were older (>40 years old) and who were employed, had higher social capital. Further research needs to be conducted to determine the relationship between social capital and HIV treatment outcomes. Public health policy-makers should adopt policies that are focused on individual younger than 18 years. Promoting youth organizations and family support is crucial to reinforce social capital in young adults. It is equally important policy to target unemployed people. Proactive decisions need to be made for the development of social networks that can facilitate and encourage collective and mutual actions and cooperation.
A thesis submitted in partial fulfilment of the requirements for the degree of MASTER OF SCIENCE IN EPIDEMIOLOGY AND BIOSTATISTICS School of Public Health, Faculty of Health Sciences University of the Witwatersrand, Johannesburg June 2015